2011
DOI: 10.1038/ijo.2011.212
|View full text |Cite
|
Sign up to set email alerts
|

The current standard measure of cardiorespiratory fitness introduces confounding by body mass: the DR's EXTRA study

Abstract: OBJECTIVE: Cardiorespiratory fitness is currently estimated by dividing maximal oxygen consumption (VO 2max ) by body weight (per-weight standard). However, the statistically correct way to neutralize the effect of weight on VO 2max in a given population is adjustment for body weight by regression techniques (adjusted standard). Our objective is to quantify the bias introduced by the per-weight standard in a population distributed across different categories of body mass. DESIGN: This is a cross-sectional stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 23 publications
6
28
0
Order By: Relevance
“…Therefore, dividing VO 2max uptake by total body weight (i.e., lean mass + fat mass) systematically underestimates cardiorespiratory fitness in obese individuals. Our research group has demonstrated both, the introduction of a substantial body-composition bias if VO 2max is divided by total body weight [3] and the elimination of body-composition bias if VO 2max is divided by lean mass [4]. These results agree with the previous finding of others that VO 2max follows a linear function of lean mass [5].…”
Section: To the Editorsupporting
confidence: 91%
“…Therefore, dividing VO 2max uptake by total body weight (i.e., lean mass + fat mass) systematically underestimates cardiorespiratory fitness in obese individuals. Our research group has demonstrated both, the introduction of a substantial body-composition bias if VO 2max is divided by total body weight [3] and the elimination of body-composition bias if VO 2max is divided by lean mass [4]. These results agree with the previous finding of others that VO 2max follows a linear function of lean mass [5].…”
Section: To the Editorsupporting
confidence: 91%
“…This is all the more remarkable, as we have shown recently that in the same population that VO 2max expressed as ml oxygen uptake per minute and kg body weight systematically underestimates cardiorespiratory fitness in obese subjects. 32 As obesity is both, a major risk factor for T2D and a link in the chain of causation between diet and T2D, one would have expected a weakening of all diet-prediabetic state associations upon adjustment for VO 2max .…”
Section: Discussionmentioning
confidence: 99%
“…Use of the weight ratio method to standardize for body size overestimates the VO 2 max for lighter individuals and underestimates it for heavier individuals. 6,7,[9][10][11] As a result, the division creates a spurious association with other variables, such as insulin sensitivity, as illustrated in a study of overweight Hispanic youth. 12 The primary aim of our analysis is to demonstrate the differences that arise when ratios, rather than partial correlation coefficients, are used to standardize VO 2 max in determining its correlation with insulin sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…dividing VO 2 max by weight, or VO 2 max/WT) is common both in research and in clinical practice. [5][6][7][8][9][10][11] The purpose of such division is presumably to create a new variable that is independent of weight. Division by weight, however, generally fails to accomplish this.…”
Section: Introductionmentioning
confidence: 99%